Automated telephone communication systems for preventive healthcare and management of long‐term conditions - Posadzki, Pawel (2018)
Background: Automated telephone communication systems (ATCS) can deliver voice messages and collect health‐related information from patients using either their telephone's touch‐tone keypad or voice recognition software. ATCS can supplement or replace telephone contact between health professionals and patients. There are four different types of ATCS: unidirectional (one‐way, non‐interactive voice communication), interactive voice response (IVR) systems, ATCS with additional functions such as access to an expert to request advice (ATCS Plus) and multimodal ATCS, where the calls are delivered as part of a multicomponent intervention. Objectives: To assess the effects of ATCS for preventing disease and managing long‐term conditions on behavioural change, clinical, process, cognitive, patient‐centred and adverse outcomes. Search methods: We searched 10 electronic databases (the Cochrane Central Register of Controlled Trials; MEDLINE; Embase; PsycINFO; CINAHL; Global Health; WHOLIS; LILACS; Web of Science; and ASSIA); three grey literature sources (Dissertation Abstracts, Index to Theses, Australasian Digital Theses); and two trial registries (www.controlled‐trials.com; www.clinicaltrials.gov) for papers published between 1980 and June 2015. Selection criteria: Randomised, cluster‐ and quasi‐randomised trials, interrupted time series and controlled before‐and‐after studies comparing ATCS interventions, with any control or another ATCS type were eligible for inclusion. Studies in all settings, for all consumers/carers, in any preventive healthcare or long term condition management role were eligible. Data collection and analysis: We used standard Cochrane methods to select and extract data and to appraise eligible studies. Main results: We included 132 trials (N = 4,669,689). Studies spanned across several clinical areas, assessing many comparisons based on evaluation of different ATCS types and variable comparison groups. Forty‐one studies evaluated ATCS for delivering preventive healthcare, 84 for managing long‐term conditions, and seven studies for appointment reminders. We downgraded our certainty in the evidence primarily because of the risk of bias for many outcomes. We judged the risk of bias arising from allocation processes to be low for just over half the studies and unclear for the remainder. We considered most studies to be at unclear risk of performance or detection bias due to blinding, while only 16% of studies were at low risk. We generally judged the risk of bias due to missing data and selective outcome reporting to be unclear...